‘Yang Indah-Indah’: Language and Ideology in Discourse of Pantun of Dewan Negara 14th Parliament - MUHAMMAD QHIDIR, MAT ISA (Parliament of Malaysia, 2023)
As the oldest Malay literary art form, Pantun aspires to the creation of ‘yang indah-indah’. In addition to the harmonious musical elements, vivid alternate rhymes that are both perceived, the beauty of a Pantun lies in its ability to convey deductive meanings using solid and transcendental allegory. For this reason, politicians are inclined to make use of this art form as a discursive strategy in political discussions despite its brevity due to its accurate, concise, and captivating quality and its deep effect on readers. Consequently, discourse Pantun becomes one of the important sources of explanation of the phenomena of language and power that take place in political discourse. Therefore, this study aims to elucidate the relationship between language and power that exist in Pantun forms, as well as to analyse the principles that support the aesthetics of Pantun recited in the Fourteenth Parliament of Senate Assembly’s Hansard text. Van Djik’s Ideological Square Scheme within the Critical Discourse Analysis is applied, along with Muhammad Haji Salleh’s literary theory Puitika Sastera Melayu (PSM). In short, in addition to its procedural function, it was found that poetry plays an important role in generating binary polarization through various discursive strategy such as Evidentiality, Self-Glorification, Victimisation, Burden, Lexicalisation, Illustration, Argumentation, Generalisasion and Metaphore. The selection of Pantun in this study dynamically and relatively fulfilled all six principles of ‘yang indah-indah’ of PSM theory.